H-NS regulation of virulence gene expression in enteroinvasive Escherichia coli harboring the virulence plasmid integrated into the host chromosome. - Colonna, B (1995)
We have previously shown that integration of the virulence plasmid pINV into the chromosome of enteroinvasive Escherichia coli and of Shigella flexneri makes these strains noninvasive (C. Zagaglia, M. Casalino, B. Colonna, C. Conti, A. Calconi, and M. Nicoletti, Infect. Immun. 59:792-799, 1991). In this work, we have studied the transcription of the virulence regulatory genes virB, virF, and hns (virR) in wild-type enteroinvasive E. coli HN280 and in its pINV-integrated derivative HN280/32. While transcription of virF and of hns is not affected by pINV integration, transcription of virB is severely reduced even if integration does not occur within the virB locus. This indicates that VirF cannot activate virB transcription when pINV is integrated, and this lack of expression accounts for the noninvasive phenotype of HN280/32. Virulence gene expression in strains HN280 and HN280/32, as well as in derivatives harboring a mxiC::lacZ operon fusion either on the autonomously replicating pINV or on the integrated pINV, was studied. The effect of the introduction of plasmids carrying virB (pBNI) or virF (pHW745 and pMYSH6504), and of a delta hns deletion, in the different strains was evaluated by measuring beta-galactosidase activity, virB transcription, and virB-regulated virulence phenotypes like synthesis of Ipa proteins, contact-mediated hemolysis, and capacity to invade HeLa cells. The introduction of pBN1 or of the delta hns deletion in pINV-integrated strains induces temperature-regulated expression or temperature-independent expression, respectively, of beta-galactosidase activity and of all virulence phenotypes, while an increase in virF gene dosage does not, in spite of a high-level induction of virB transcription. Moreover, a wild-type hns gene placed in trans fully reversed the induction of beta-galactosidase activity due to the delta hns deletion. These results indicate that virB transcription is negatively regulated by H-NS both at 30 and at 37 degrees C in pINV-integrated strains and that there is also a dose-dependent effect of VirF on virB transcription. The negative effect of H-NS on virB transcription at the permissive temperature of 37 degrees C could be due to changes in the DNA topology occurring upon pINV integration that favor more stable binding of H-NS to the virB promoter DNA region. At 30 degrees C, the introduction of the high-copy-number plasmid pMYSH6504 (but not of the low-copy-number pHW745) or of the deltahns deletion induces, in strains harboring an autonomously replicating pINV, beta-galactosidase activity, virB transcription, and expression of the virulence phenotypes, indicating that, as for HN280/32, the increase in virF gene dosage overcomes the negative regulatory effect of H-NS on virB transcription. Moreover, we have found that virF transcription is finely modulated by temperature and, with E. coli K-12 strains containing a virF-lacZ gene fusion, by H-NS. This leads us to speculate that, in enteroinvasive bacteria, the level of Virf inside the cell controls the temperature-regulated expression of invasion genes.